HUBUNGAN SOSIAL EKONOMI DAN ASUPAN ZAT GIZI DENGAN KEJADIAN KURANG ENERGI KRONIK (KEK) PADA IBU HAMIL DI WILAYAH PUSKESMAS SEI JANG KECAMATAN BUKIT BESTARI KOTA TANJUNG PINANG TAHUN 2016 - Gotri Marsedi Siahaan; Laksmi Widajanti; Ronny Aruben (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Health development in the field of nutrition services is done to improvemen t of nutrition troughout the life cycle since in the womb until elderly with prone to malnutrition group’s priority.The problem of malnutrition in pregnant woman at this time is the focus of attention, because the problem is very dangerous especially to pregnant woman who have anemia and Chronic Energy Deficiency. Nutritional problems that occur caused by several factors either directly or not. The purpose of this study was conducted to determine the relationship between socio-economic variables and nutrient intake with the incidence of Chronic Energy Deficiency in pregnant women. The form of research ,mis quantitative research that use observational analytic approach Cross sectional with Chronic Energy Deficiency are 27 people and Non-chronic Energy Deficiency are 47 people, so total sample are 74 people. Data were obtained by interview and questionnaire method. Data was analyzed using Chi Square test. The results of this study indicate that the educational variables (0.561> of 0.05), Job (0.272> 0.05), income (0.550> 0.05) and indicate Energy intake ( 0,006 <0,05) , protein intake (0,003 <0,05) and fat intake (0,000 <0,05) The conclusion of this research is that there is no correlation between socio-economic variables (education, occupation, and income) with Chronic Energy Deficiency in pregnant women and in nutritional intake variable (energy, protein, and fat) have correlation with Chronic Energy Deficiency in pregnant women